Nitric oxide negatively regulates c-Jun N-terminal kinase/stress-activated protein kinase by means of S-nitrosylation - Park, Hee-Sae (The National Academy of Sciences, 2000)
NO, produced from l-arginine in a reaction catalyzed by NO synthase, is an endogenous free radical with multiple functions in mammalian cells. Here, we demonstrate that endogenously produced NO can suppress c-Jun N-terminal kinase (JNK) activation in intact cells. Treatment of BV-2 murine microglial cells with IFN-γ induced endogenous NO production, concomitantly suppressing JNK1 activation. Similarly, IFN-γ induced suppression of JNK1 activation in RAW264.7 murine macrophage cells and rat alveolar macrophages. The IFN-γ-induced suppression of JNK1 activation in BV-2, RAW264.7, or rat alveolar macrophage cells was completely prevented by N(G)-nitro-l-arginine, a NO synthase inhibitor. Interestingly, the IFN-γ-induced suppression of JNK1 activation was not affected by 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one, an inhibitor of guanylyl cyclase. 8-Bromo-cGMP, a membrane-permeant analogue of cGMP, did not change JNK1 activation in intact cells either. In contrast, S-nitro-N-acetyl-dl-penicillamine (SNAP), a NO donor, inhibited JNK1 activity in vitro. Furthermore, a thiol reducing agent, DTT, reversed not only the in vitro inhibition of JNK1 activity by SNAP but also the in vivo suppression of JNK1 activity by IFN-γ. Substitution of serine for cysteine-116 in JNK1 abolished the inhibitory effect of IFN-γ or SNAP on JNK1 activity in vivo or in vitro, respectively. Moreover, IFN-γ enhanced endogenous S-nitrosylation of JNK1 in RAW264.7 cells. Collectively, our data suggest that endogenous NO mediates the IFN-γ-induced suppression of JNK1 activation in macrophage cells by means of a thiol-redox mechanism.